Gamification in Psychological Therapy: A Literature Review of Creative Engagement Techniques in Mental Health Interventions - Habib Priyono; Annas Alkhowarizmi; Rudi Setiawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This literature review explores the application of gamification as an innovative strategy to enhance engagement in psychological therapy. The study systematically examined 32 peer-reviewed articles published between 2015 and 2024, focusing on interventions that utilized game-based elements such as points, levels, narratives, and avatars to improve mental health outcomes. The review identifies that gamified interventions are particularly effective among adolescents and young adults, demonstrating increased motivation, treatment adherence, and emotional resilience. However, the findings also reveal critical challenges, including ethical concerns, inconsistent long-term outcomes, and limited applicability in culturally diverse populations. By synthesizing theoretical frameworks and empirical evidence, this paper highlights the potential of gamification to transform therapeutic approaches while emphasizing the need for rigorous design, ethical oversight, and continued research. The study contributes to the growing discourse on integrating digital innovation with psychological practice to expand access and improve mental health care delivery.